Troubling American women : narratives of gender and nation in Hong Kong - Ford, Stacilee (Hong Kong University Press, 2011)
This book analyzes the cultural production (narratives) of selected American, Chinese American, and "Americanized" Chinese women who lived in Hong Kong and Macao during the nineteenth and twentieth centuries. It focuses on the diverse ways women envisioned and communicated their notions of national identity depending on individual circumstance and historical era.